2 Simpify:
a -4 X x = -4x
b -10 X y = -10y
c -1 X a = -a
d b X (-1) = -b
e -4 X 2m = -8m
f 6 X -3a = -18a
g -8 X -3a = 24a
h -6m X 4 = -24m
i -7 X 8n = -56n
j -a X -3 = 3a
k 6x / -2 = -3x
l -10m / -5 = 2m
m -24a / 8 = -3a
n 2(m+3)-8=2(m)+2(3)-8=2m+6-8=2m-2
o 5(m-1)+9=5(m)+5(-1)+9=5m-5+9=5m+4
p 3(a-5)+10=3(a)+3(-5)+10=3a-15+10=3a-5
q 4(2x+1)-8x=4(2x)+4(1)-8x=8x+4-8x=4
r 3(10-2x)+3x=3(10)+3(-2x)+3x=30-6x+3x=30-3x
s 4(3-x)+9x=4(3)+4(-x)+9x=12-4x+9x=12+5x
3 Simplify by collecting like terms:
a 7a-5b+2a-6b=(7+2)a+(-5-6)b=(9)a+(-11)b=9a-11b
b 11x-2y-5x+7y=(11-5)x+(-2+7)y=(6)x+(5)y=6x+5y
c 3m+2g-5g-4m=(3-4)m+(2-5)g=(-1)m+(-3)g=-m-3g
d 6a-7-9a+10=(6-9)a+(-7+10)=(-3)a+(3)=-3a+3
e 7p-2q-6p+3q=(7-6)p+(-2+3)q=(1)p+(1)q=p+q
f 3x+7-12-5x=(3-5)x+(7-12)=(-2)x+(-5)=-2x-5
g 2ab+3bc-5ab+bc=(2-5)ab+(3+1)bc=(-3)ab+(4)bc=-3ab+4bc
h 6t^2+3t-5t^2-8t=(6-5)t^2+(3-8)t=(1)t^2+(-5)t=t^2-5t
i 9y-6z-9y+5z=(9-9)y+(-6+5)z=(0)y+(-1)z=0-z=-z
j 2k-3k^2-4k+k^2=(2-4)k+(-3+1)k^2=(-2)k+(-2)k^2=-2k-2k^2
k 10t+5w+t-7w=(10+1)t+(5-7)w=(11)t+(-2)w=11t-2w
l 7a-3b-8a-5b=(7-8)a+(-3-5)b=(-1)a+(-8)b=-a-8b
The <em>correct answer</em> is:
C) The quantity of distance measured in feet depends on the quantity of time measured in minutes.
Explanation:
The rate of an airplane's descent would be found using the distance it descends and the amount of time that takes.
In this situation, the amount of time that passes causes the distance the plane descends to change; this means that the distance depends on the time.
Answer:
x=18
Step-by-step explanation:
Answer:
g(1) = -6
Step-by-step explanation:
g(x) = -2x^2 - 4x
You want to solve for g(1). To do this make every x value in the original equation become 1.
g(1) = -2(1)^2 - 4(1)
Evaluate the exponent.
g(1) = -2(1) - 4(1)
Multiply.
g(1) = -2 - 4
Subtract.
g(1) = -6
Answer:
x=4.25
Step-by-step explanation:
4x=17
4x/4=17/4
x=17/4
or
x=4.25
Hope this helps .-.